Contemporary Kazakh literature: Post-Socialist Contexts and Artistic Translations (Eurasian Journal of Philology Science and Education, 2023)
The change of the modern world determines the transformation of the principles of dialogicity under the influence of a single global communicative space. The literature of Kazakhstan continues intercultural interaction and develops a productive dialogue with the national literatures of the world in the XXI century. The development of the latest scientific research in the study of Kazakh literature and the literature of the ethnic groups of the country, their perception in international contexts in line with the post-non-classical period of science and postcolonial theory in literary studies are relevant and in demand today.The authors of the article consider the study of the spiritual image of the Kazakh people and culture in the perception of the foreign environment and multicultural space to be relevant and important. There were, as is known, international and interethnic interactions important for Kazakh literature in the past. There are new factors and communications affecting the state of literature in Kazakhstan today. The audiovisual and computer industry determine the expansion of discourses of the study of Russian culture and literature in the axiological aspect of modern philological research. The range of reception of Kazakh literature abroad is constantly expanding. The dynamic and progressive development of foreign relations is justified by the fact that Kazakh-English, Azerbaijani, American, Belarusian, Bulgarian, Czech and Georgian cooperation opens up new prospects for the study of Kazakh literature in international contexts in the aspect of post-non-classical epistemology and plurality.The research methodology is based on a combination of historical-typological and hermeneutic methods. The method of culturological interpretation of texts in the native literary environment and in a foreign one, in which it is included in the process of literary translation, is also important. The results of the article will be of some scientific interest in the country and abroad.